The writing on the wall: Identity, placemaking and territoriality in Karachi's graffiti culture - Sadaf Sultan Khan (Wellbeing, Space and Society)
This article explores the spatiality of political graffiti and urban murals and the role they play in placemaking, territoriality and identity building amongst Karachi's migrant communities. From Independence in 1947 to the present day, the city has been the site of several waves of in-migration, both domestic and international, resulting in a migrant megacity. Through shared migration experiences and cultural heritage, political patronage and spatial clustering, communities have consolidated and reimagined ethnic identities into political ones. These ethno-political entities demarcate territories of dominance and spaces of tension using political graffiti. This tool for placemaking and territory marking is an urban declaration of power on the walls of the city. More recently, political graffiti has been deliberately replaced by civil society actors in the form of murals changing the provocative ethno-political sloganeering to a nationalistic counter narrative. With multiple actors – political and apolitical - sentiments and stories now vying for space through their occupation of the city's walls, these surfaces become spaces of declaration, dialogue and at times, erasure. Through a process of diachronic documentation, this article shows that the walls of the city are a palimpsest of political opinion and identity; each subsequent layer in dialogue with the layer that precedes it. The authors of each layer through a process of placemaking, construct, deconstruct and reconstruct narratives of identity, ownership and belonging.